Estratégias de enfrentamento de mulheres vítimas de violência doméstica - Lincoln, Leila Estevão da Silva Cacciacarro (Universidade Federal de São Carlos, 2013)
The aim of this work is domestic violence and coping strategies used by women victims of this violence. Violence against women can be characterized by the interaction of husband / partner to intimidate, threaten, make use of physical force as well as doing something against the property of the woman. The main forms of violence against women are: physical violence, sexual violence, psychological violence and destruction of property. Coping can be understood as a set of cognitive and behavioral efforts with regard to dealing with internal or external demands that arise in stress situations. The research aimed to identify and describe the coping strategies of women who have suffered or are suffering domestic violence and as specific objectives to categorize coping strategies of women victims of domestic violence, characterize the history of violence suffered by women and finally characterize the severity of violence against the women. This was a qualitative research, exploratory kind. The choice, assembly and appropriateness of the instrument was made, being: semi-structured interview, applied individually to women victims of domestic violence. Before the data collection, there was a testing tool to estimate the time of application and suitability. After approval of the ethics committee, and the proper clarifications of the research, attended to the interview 4 women victims of domestic violence. As a result, it may be highlight that all women participants suffered psychological and physical violence, whereas two women also reported having suffered sexual violence. Regarding the severity of the violence suffered, women present level 5, 4, 3 and 2 respectively. Women had the following categories of coping strategies: removal, self-control, social support, escape-avoidance, problem solving, positive reappraisal, leisure and finally, plans for the future. Domestic violence, like any other type of violence, characterized as a violation of human rights and fundamental freedoms, which limits women the recognition, enjoyment or exercise of any right as well as the exercise of freedom. It is considered necessary the creation of public policies that will help minimize the victimization of women who suffer domestic violence, and to develop coping strategies. That this work will contribute to the construction of preventive practices that provide coping strategies such as confrontation, distancing, self-control, social support, escape-avoidance, problem solving, positive reappraisal, leisure and plans for the future. After all, it was verified that these strategies could break with some cases of severe violence.
Coping Strategies for Women Victims of Domestic
Keywords: Educação especial; Violência conjugal; Estratégia de Enfrentamento; Severidade da Violência; ViolenceSpecial Education; Domestic Violence; Coping Strategy; Severity of Violence; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL